1995
DOI: 10.1084/jem.181.3.839
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin 10 in the B lymphocyte hyperactivity and autoantibody production of human systemic lupus erythematosus.

Abstract: SummaryInterleukin-10 (IL-10) is produced at a high level by B lymphocytes and monocytes of patients with systemic lupus erythematosus (SLE). In the present work, we analyzed whether this increased production of IL-10 contributed to the abnormal production of immunoglobulins (Ig) and of autoantibodies in SLE. The role of IL-10 was compared with that of IL-6, another cytokine suspected to play a role in these abnormalities. The spontaneous in vitro production of IgM, IgG, and IgA by peripheral blood mononuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
326
1
7

Year Published

1997
1997
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(348 citation statements)
references
References 23 publications
14
326
1
7
Order By: Relevance
“…On the other hand, our data indicate that IFN-g, the cytokine whereby T cells usually mediate the effects of IL-12 in vivo [7,9,17,18], is not implicated in the inhibition exerted by IL-12 on lupus B lymphocytes. Finally, the critical role played by IL-10 in SLE B cell activation [1,3] prompted us to test the possibility that the negative effects of IL-12 on immunoglobulin production were due to down-regulation of endogenous IL-10 production, the more so as IL-10 production by CD4 þ allergen-specific human T cells was shown to be inhibited by IL-12 [22]. Interestingly, IL-10 production was significantly down-regulated in lupus PBMC cultures stimulated with IL-12, an effect that was attributed to IFN-g up-regulation by IL-12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our data indicate that IFN-g, the cytokine whereby T cells usually mediate the effects of IL-12 in vivo [7,9,17,18], is not implicated in the inhibition exerted by IL-12 on lupus B lymphocytes. Finally, the critical role played by IL-10 in SLE B cell activation [1,3] prompted us to test the possibility that the negative effects of IL-12 on immunoglobulin production were due to down-regulation of endogenous IL-10 production, the more so as IL-10 production by CD4 þ allergen-specific human T cells was shown to be inhibited by IL-12 [22]. Interestingly, IL-10 production was significantly down-regulated in lupus PBMC cultures stimulated with IL-12, an effect that was attributed to IFN-g up-regulation by IL-12.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in our understanding of the biology of cytokines have shed new light on the mechanisms underlying this inappropriate antibody production. Thus, it was demonstrated that IL-10 is overexpressed in lupus patients [1,2] and mediates, at least in part, the excessive immunoglobulin production and the autoantibody response associated with human and murine SLE [3,4]. Such results demonstrate that cytokines are closely involved in the pathogenesis of lupus and suggest that cytokine manipulation might be useful for the control of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…3 Contrary to its inhibitory function in T cells and macrophages, in B cells IL-10 stimulates the production of immunoglobulins and the expression of MHC class II antigens. 4 IL-10 has a central role in the pathogenesis of autoimmune diseases like systemic lupus erythematosus (SLE) 5 and influences susceptibility and the course of various infectious diseases. [6][7][8] The constitutive expression of IL-10 in monocytes and lymphocytes is low.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Therefore, IL10 production may contribute to the disease by direct effect on B cell survival and on autoantibody production. 8 Moreover, B cells and monocytes of SLE patients produce an increased amount of IL10 compared to non-affected individuals. 9,10 Besides its functional relevance, IL10 is an attractive positional candidate gene since it maps in 1q32, in a region homologous to a murine SLE susceptibility region (reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%